2015
DOI: 10.1073/pnas.1505962112
|View full text |Cite
|
Sign up to set email alerts
|

Telomeric repeat-containing RNA (TERRA) constitutes a nucleoprotein component of extracellular inflammatory exosomes

Abstract: Telomeric repeat-containing RNA (TERRA) has been identified as a telomere-associated regulator of chromosome end protection. Here, we report that TERRA can also be found in extracellular fractions that stimulate innate immune signaling. We identified extracellular forms of TERRA in mouse tumor and embryonic brain tissue, as well as in human tissue culture cell lines using RNA in situ hybridization. RNA-seq analyses revealed TERRA to be among the most highly represented transcripts in extracellular fractions de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
76
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(81 citation statements)
references
References 68 publications
4
76
0
1
Order By: Relevance
“…Based on these data and our recently published study, 20 we propose that telomere-induced stress leads to the upregulation of TERRA that is processed into smaller fragments and secreted in exosome-like vesicles. These TERRA containing exosomes are relatively stable and circulate in extracellular spaces, including blood and plasma.…”
Section: Inflammatory Properties Of Exosomal Terrasupporting
confidence: 70%
See 3 more Smart Citations
“…Based on these data and our recently published study, 20 we propose that telomere-induced stress leads to the upregulation of TERRA that is processed into smaller fragments and secreted in exosome-like vesicles. These TERRA containing exosomes are relatively stable and circulate in extracellular spaces, including blood and plasma.…”
Section: Inflammatory Properties Of Exosomal Terrasupporting
confidence: 70%
“…10 We previously demonstrated that exosomal TERRA is smaller than cellular TERRA, and is associated with a small percentage of telomeric DNA and histone protein components. 20 Using identical extraction methods described previously, we measured exosome-associated TERRA by dot blot (Fig. 1C).…”
Section: Terra Is Highly Enriched In Human Exosomesmentioning
confidence: 99%
See 2 more Smart Citations
“…55 Telomeric repeat-containing RNA (TERRA) is release into exosomes by cells that present telomere dysfunction. 56,57 Although several works have reported the presence of DNA in exosomes, the function of exosomes in the regulation of DNA homeostasis is far from been elucidated.…”
mentioning
confidence: 99%